2014
DOI: 10.3384/diss.diva-106483
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of a ventilation strategy – impinging jet ventilation for an office environment

Abstract: A well-functioning, energy-efficient ventilation system is of vital importance to offices, not only to provide the kind of comfortable, healthy indoor environment necessary for the well-being and productive work performance of occupants, but also to reduce energy use in buildings and the associated impact of CO 2 emissions on the environment. To achieve these goals impinging jet ventilation has been developed as an innovative ventilation concept.In an impinging jet ventilation system, a high momentum of air je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Currently, the devices are widely used in offices, in addition to solar energy conditions, can cause high heat loads in these enclosed spaces. These problems will pose challenges to the ventilation of office buildings [8]. Although the specific factors commitment to ventilation problems are not known, several studies have shown that most diseases and complaints are Due to poor indoor air quality and noticeable physical disturbance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the devices are widely used in offices, in addition to solar energy conditions, can cause high heat loads in these enclosed spaces. These problems will pose challenges to the ventilation of office buildings [8]. Although the specific factors commitment to ventilation problems are not known, several studies have shown that most diseases and complaints are Due to poor indoor air quality and noticeable physical disturbance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Heat generation from multiple devices results in an increase in indoor heat in an office environment, as well as solar conditions, resulting in increased heat load. This found challenges for office room ventilation, (Chen ,2014(. More than 90% of people's time is spent in a closed climate, so maintaining health in the indoor environment is an important factor, (Awbi ,2003) and (Turiel ,1985).…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory disease was Abnormally observed in many countries of the world. Several recent studies have proven that most diseases are due to poor indoor air quality, (Chen ,2014) and (Turiel ,1985). Building ventilation has been systematically studied as a dynamic system for more than (100) years, (Viley and Halsted;1858), ( Roberts,1892).…”
Section: Introductionmentioning
confidence: 99%
“…Ventilation with stratified air distribution and partially increased vertical temperature gradient can contribute to efficient heat removal and energy saving in comparison with mixing ventilation with uniform indoor air temperature (Cehlin and Moshfegh 2010;Chen 2014;Nielsen and Awbi 2008;Lin et al 2009;Tian, Lin, and Wang 2011). In the stratified ventilations, cold air enters the occupant region at low height levels.…”
Section: Air and Surface Temperature Gradientsmentioning
confidence: 99%